Generalization and discrimination of inhibitory avoidance differentially engage anterior and posterior retrosplenial subregions - Met Hoxha, Erisa; Robinson, Payton K.; Greer, Kaitlyn M.; Trask, Sydney (Frontiers in Behavioral Neuroscience, 2024)
Introduction In a variety of behavioral procedures animals will show selective fear responding in shock-associated contexts, but not in other contexts. However, several factors can lead to generalized fear behavior, where responding is no longer constrained to the conditioning context and will transfer to novel contexts. Methods Here, we assessed memory generalization using an inhibitory avoidance paradigm to determine if generalized avoidance behavior engages the retrosplenial cortex (RSC). Male and female Long Evans rats received inhibitory avoidance training prior to testing in the same context or a shifted context in two distinct rooms; one room that had fluorescent lighting (Light) and one that had red LED lighting (Dark). Results We found that animals tested in a light context maintained context-specificity; animals tested in the same context as training showed longer latencies to cross and animals tested in the shifted context showed shorter latencies to cross. However, animals tested in the dark generalized their avoidance behavior; animals tested in the same context and animals tested in the shifted context showed similarly-high latencies to cross. We next examined expression of the immediate early gene zif268 and perineuronal nets (PNNs) following testing and found that while activity in the basolateral amygdala corresponded with overall levels of avoidance behaviors, anterior RSC (aRSC) activity corresponded with learned avoidance generally, but posterior RSC (pRSC) activity seemed to correspond with generalized memory. PNN reduction in the RSC was associated with memory formation and retrieval, suggesting a role for PNNs in synaptic plasticity. Further, PNNs did not reduce in the RSC in animals who showed a generalized avoidance behavior, in line with their hypothesized role in memory consolidation. Discussion These findings suggest that there is differential engagement of retrosplenial subregions along the rostrocaudal axis to generalization and discrimination.